From sentinel cells to inflammatory culprits: cancer‐associated fibroblasts in tumour‐related inflammation. (20th November 2012) - Servais, Charlotte; Erez, Neta
Abstract Inflammation is now established as a hallmark of cancer. Cancer‐associated fibroblasts (CAFs) have been established as a key component of the crosstalk between tumour cells and their microenvironment. Central to the role of CAFs in facilitating tumour growth, invasion, and metastasis is their ability to orchestrate tumour‐related inflammation. CAFs and their soluble mediators provide multiple complex regulatory signals that modulate the trafficking, differentiation status, and function of inflammatory cells in the tumour microenvironment. This review focuses on pathways by which CAFs mediate tumour‐promoting inflammation and modify the components of the inflammatory microenvironment that facilitate tumour initiation, progression, and metastasis.Copyright © 2012 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.